2013
DOI: 10.1016/j.chemosphere.2013.06.077
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of heavy metal polluted soils using Sedum plumbizincicola inoculated with metal mobilizing Phyllobacterium myrsinacearum RC6b

Abstract: h i g h l i g h t sIsolated Phyllobacterium myrsinacearum RC6b effectively mobilized metals in soils. RC6b inoculation enhanced growth and Cd and Zn uptake of Sedum plumbizincicola. Possible mechanisms are plant beneficial activities and soil metal mobilization. RC6b is a good candidate for microbially assisted phytoremediation. a r t i c l e i n f o t r a c tThe aim of this study was to investigate the effects of metal mobilizing plant-growth beneficial bacterium Phyllobacterium myrsinacearum RC6b on plant g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 142 publications
(39 citation statements)
references
References 37 publications
(52 reference statements)
3
32
1
3
Order By: Relevance
“…Similar results were reported in studies of cadmium accumulation in Juncus subsecundus and Sedum alfredii (Li and Wong, 2012). Previous studies reported that inoculation of metalresistant bacteria could increase the metal accumulation in plants (Chen et al, 2014;Ma et al, 2013), and organic pollutant-degrading bacterial inoculation also could enhance plants to accumulate more heavy metals . The increased metal accumulation by mushrooms after inoculation of metal-resistant microbes also have been reported (Ji et al, 2012;Jing et al, 2012).…”
Section: Accumulation In P Cornucopiae Under Joint Stress Of CD Asupporting
confidence: 88%
“…Similar results were reported in studies of cadmium accumulation in Juncus subsecundus and Sedum alfredii (Li and Wong, 2012). Previous studies reported that inoculation of metalresistant bacteria could increase the metal accumulation in plants (Chen et al, 2014;Ma et al, 2013), and organic pollutant-degrading bacterial inoculation also could enhance plants to accumulate more heavy metals . The increased metal accumulation by mushrooms after inoculation of metal-resistant microbes also have been reported (Ji et al, 2012;Jing et al, 2012).…”
Section: Accumulation In P Cornucopiae Under Joint Stress Of CD Asupporting
confidence: 88%
“…Similar phenomenon was reported before when phytochelatins increased long-distance root-to-shoot Cd 2+ transport and reduce Cd 2+ accumulation in roots (Gong, Lee and Schroeder 2003). Recently, Ma et al (2013) also reported an isolated strain of Phyllobacterium myrsinacearum RC6b effectively mobilized metals in soils and the RC6b inoculation enhanced growth and Cd and Zn uptake of Sedum plumbizincicola. In addition, Wang et al (2011) demonstrated that Agrobacterium radiobacter D14, which secreted the indole acetic acid and siderophore, increased the As tolerance of P. deltoides by promoting growth, increasing uptake efficiency, and enhancing As translocation.…”
Section: Figsupporting
confidence: 83%
“…Mineral phosphate solubilization activity was assayed according to Kuklinsky-Sobral et al (2004). Indoleacetic acid (IAA) production was analyzed using a modified qualitative method (Ma et al 2013), and the ability of nitrogen fixing was estimated according to Mohan and Rajendran (2014). After being treated with Salkowski reagent for 30 min, appearance of a pale pink ring on the filter paper from LB medium was positive for the IAA assay.…”
Section: Plant Growth-promoting Charactersmentioning
confidence: 99%